A Case Study of Epstein-Barr Virus–Associated Extranodal Lymphoid Hyperplasia of Rectal Tonsillar Lesion in an Immunocompetent Female Patient. (21st September 2018) - Soliman, Mahmoud; Zhao, Qing; O'Hara, Carl
Abstract: Epstein-Barr virus (EBV) infection is associated with a number of malignancies such as diffuse large B-cell lymphoma, Burkitt lymphoma, Hodgkin lymphoma, and nasopharyngeal carcinoma. Rectal tonsil is a reactive proliferation of benign lymphoid tissue in the rectum. Whereas EBV-related lymphoid hyperplasia is well described in the palatine tonsil in infectious mononucleosis, we present a unique case of EBV-driven extranodal lymphoid hyperplasia of a rectal tonsillar lesion. A prominent rectal lymphoid aggregate was found in a healthy immunocompetent 57-year-old female undergoing routine screening colonoscopy. A dense infiltrate of predominantly intermediate-sized lymphocytes with dispersed nuclear chromatin and slightly prominent nucleoli was seen in the mucosa, involving the lamina propria and extending through the muscularis mucosa, therefore morphologically mimicking a high-grade lymphoma. Immunohistochemical studies revealed positive staining of the atypical lymphoid infiltrate for LCA/CD45, CD30, and the B-cell antigen pax-5 and negative staining for CD20, cytokeratins CAM5.2 and AE1/3, and the melanocytic marker SOX10. In addition, there was a prominent component of CD3-positive small lymphocytes. In situ hybridization revealed positive EBV (EBER) and monoclonal staining of plasmacytic cells for lambda light chain immunoglobulins with only occasional kappa-positive cells, further raising the suspicion for high-grade lymphoma. On the other hand, no rearrangement of the immunoglobulin heavy chain gene or T-cell receptor could be demonstrated using polymerase chain reaction. Based on the morphology of the infiltrate, the immunohistochemical studies, and in situ hybridization results, the findings are most in keeping with an EBV-driven lymphoid hyperplasia. While there are some features suggesting a lymphoproliferative disorder, convincing demonstration of B-cell monoclonality could not be established and therefore a diagnosis of lymphoma was not rendered. Awareness of this entity is of paramount importance to avoid misdiagnosing this benign lesion as lymphoma.